1977
DOI: 10.7589/0090-3558-13.3.273
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS ON THE SEASONAL PREVALENCE, PATHOLOGY AND TRANSMISSION OF Dracunculus insignis (NEMATODA: DRACUNCULOIDEA) IN THE RACCOON (Procyon lotor (L.) IN ONTARIO

Abstract: Lesions due to Dracunculus insignis in the legs of raccoons (Procyon lotor) in southern Ontario occur seasonally as most larvigerous females emerge in the spring and early summer (April-June). The pathology of dracunculiasis in the raccoon is described and the transmission of the parasite in the wild is discussed with respect to seasonality and local agricultural practices. Crayfish, fishes and frogs (including tadpoles) were given infective third-stage larvae of D. insignis to test their suitability as parate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…Although tadpoles consumed far fewer copepods, most tadpoles exposed to infected copepods subsequently had infections, which is consistent with previous data that showed a high percentage of adult frogs ( L. pipiens and L. clamitans ) acquired infections when a very high dose of infected copepods (n = 200–500) were given by mouth ( 4 ). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although tadpoles consumed far fewer copepods, most tadpoles exposed to infected copepods subsequently had infections, which is consistent with previous data that showed a high percentage of adult frogs ( L. pipiens and L. clamitans ) acquired infections when a very high dose of infected copepods (n = 200–500) were given by mouth ( 4 ). …”
Section: Discussionsupporting
confidence: 90%
“…These results, although limited in scope, clearly confirm that D. medinensis , like D. insignis , can use an aquatic paratenic host; specifically, at least 2 species of amphibians ( 4 6 ). Although tadpoles consumed far fewer copepods, most tadpoles exposed to infected copepods subsequently had infections, which is consistent with previous data that showed a high percentage of adult frogs ( L. pipiens and L. clamitans ) acquired infections when a very high dose of infected copepods (n = 200–500) were given by mouth ( 4 ).…”
Section: Discussionmentioning
confidence: 61%
“…Attempts to experimentally transmit Dracunculus insignis to the crayfish Orconectes propinquus from infected copepods were unsuccessful leading the authors to suggest that crayfish may not be a suitable host for this nematode (Crichton and Beverley-Burton, 1977). Quaglio et al (2006b) reported unidentified nematodes encysted in the intestines of P. clarkii but were unable to ascertain the role of crayfish in the life cycle of the parasite; no pathology was reported for this infection.…”
Section: Nematodamentioning
confidence: 95%
“…In such cases, only heavy infections may be damaging, while light infections lead to minor physiological disturbance or sub-clinical debilitation. This is known to occur with nematode burdens in both fish and terrestrial animals (Crichton & Beverley-Burton, 1977;Sekretaryuk, 1980Sekretaryuk, , 1983Gulland, 1992). The third possibility is that the parasite is pathogenic only to very small fish (Wierzbicki, 1958;Vasilkov, 1983;Moravec, 1994), being tolerated once crucian carp attain a certain size.…”
Section: Discussionmentioning
confidence: 99%